Модель оцінювання можливостей процесу іт-компанії - Євланов, М.; Неумивакіна, О.; Корнєєва, Є. (ХНУРЕ, 2018)
Проаналізовано сучасні підходи до оцінювання рівнів можливостей процесів. Визначено атрибути процесу як оцінки рівнів окремого процесу. Розроблено модифікацію теоретико-категорної моделі аналітичного представлення автоматизованого бізнеспроцесу. Запропонована модифікація дозволяє використовувати теоретико-категорну модель для оцінювання рівніві можливостей процесів ІТ-компанії. The modern approaches to estimating the levels of process possibilities are analyzed. The attributes of the process as the estimation of levels of a separate process are determined. A modification of the theoretically-categorical model of the analytical representation of the automated business process has been developed. The proposed modification allows us to use the theoretically-categorical model for estimating the level of opportunities of the processes of the IT company.
Model of Evaluation of the Capabilities of the IT Company Process
Keywords: атрибути процесу; бізнеспроцес